Mongolian Spots as a Clue to Mucopolysaccharidoses - Parmar, PN; Kalathiya, MB; Rathod, VB (Journal of Nepal Paediatric Society, 2013)
Mongolian spots are generally considered to have no clinical significance. However, if excessive or at unusual sites, they may be a clue to mucopolysaccharidoses. DOI: http://dx.doi.org/10.3126/jnps.v33i1.5758 J Nepal Paediatr Soc. 2013;33(1):83